Utilizing Project-Based Learning to Increase Engagement and Performance in the High School Classroom - Alan English (Prairie Journal of Educational Research, 2018)
Abstract Project-based learning was incorporated into a high school American History course unit where students were expected to write an original history of the Vietnam War based exclusively on primary sources. Throughout the school year, students working as a collective unit worked to raise funds at school events for the purpose of surprising a class guest speaker, a Vietnam veteran, with a sponsored flight to Washington D.C. through Kansas Honor Flights. In addition to creating an experience of civic participation, student engagement (as measured by rate of completion of the project) and performance (as measured by average grade on the project) were tracked. Statistically significant improvements with a moderate effect size were found in student engagement as compared to previous school years. No statistically significant improvements in student performance were demonstrated. Results support previous literature linking project-based learning to increased student engagement but potentially indicate that student performance is best manipulated by an alternative mechanism.
Keywords: Project-based learning; Civic participation; Engagement; Performance; Social studies; Vietnam; Kansas Honor Flights